Competitive Strategy To Improve The Performance of Raja Haji Fisabilillah International Airport In 2023 - Achmad Widyawan; Salahudin Rafi; Suharto Abdul Majid (Dinasti Publisher, 2024)
This research explores competitive strategies that are suitable for Raja Haji Fisabilillah Airport in terms of efforts to improve performance. Since 2001 PT Angkasa Pura II as the airport operator has taken over this airport because the decision to take over the airport to PT Angkasa Pura II can be seen from the performance of ATS (over flying) aero revenue.) which is very large, but since the Government established the Aviation Navigation Services Business Entity, it is deemed necessary in the future for the Company to develop a good strategy for the sustainability of airports, especially RHF Airport Branch Offices. On this basis, this paper aims to find and analyze competitive strategies that are suitable for improving airport performance as part of the strategy formulation stage. The method used in this research is the SWOT Analysis method using the Tows Matrix strategy formulation, which will produce a suitable competitive strategy under the operational performance of Raja Haji Fisabilillah Airport. The results obtained from this strategy are an increase in company revenue, and efficient use of operational expenses, thereby influencing every aspect to gain a competitive advantage.